Tasawuf sebagai Jalan Spiritual: Integrasi Akal dan Ruhani Menuju Kehidupan Abadi - Wahyudi, Eko; Abdullah, Fadli Daud; Mubin, Abdul; Sudiaman, Maman (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines Sufism as a spiritual path that integrates reason and spirit to achieve eternal life. The background of this study is based on the fact that understanding the nature of human creation cannot be separated from three main disciplines in the Islamic treasury: kalam, Islamic philosophy, and Sufism. The purpose of this study is to explore Sufism as a spiritual path that integrates reason and spirit in order to lead humans to eternal happiness. The research method used is qualitative with literature analysis from various classical and contemporary sources. The results of the discussion indicate that in the science of kalam, the nature of human creation is directed towards the primary goal of worshiping Allah and bearing moral responsibility. Meanwhile, Islamic philosophy emphasizes the importance of intellectual perfection and moral development as a path to happiness (sa'adah). Sufism, on the other hand, presents a practical method through tazkiyatun nafs (self-control), with stages of takhalli, tahalli, and tajalli as a process of purifying the soul. These three perspectives, when integrated, emphasize the position of humans as servants ('abd) and caliphs, harmonizing reason, spirit, and righteous deeds, thus forming a perfect human being, namely a complete, civilized, and spiritually mature human being for the ultimate goal of returning to Allah with a pure heart and enlightened mind. The implication in the modern era is that Sufism is not only seen as an inner path, but as a spiritual technology that guides humans through the transience of life to eternal happiness in the pleasure of Allah.   Keywords: Reason, Islamic Philosophy, Eternal Life, Kalam, Sufism